Association between disease severity and systemic inflammation in patients with dilated cardiomyopathy (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. The aim of this study was to investigate the relationship between clinical-hemodynamic parameters and inflammatory markers (C-reactive protein, interleukin-6, tumor necrosis factor-α) in patients with dilated cardiomyopathy. Materials and methods. The study included 42 patients (mean age 38.5±1.2 years) with dilated cardiomyopathy and chronic heart failure classified as NYHA functional class II–IV. The patients were divided into two groups: Group I – class II (n=12) and Group II – class III–IV (n=30). Results. As heart failure severity increased (class III–IV), serum levels of C-reactive protein (7.6±1.1 mg/L vs. 4.1±0.6 mg/L, p<0.05), IL-6 (7.5±0.8 pg/mL vs. 4.6±0.2 pg/mL, p<0.01), and TNF- α (8.1±0.9 pg/mL vs. 5.6±0.7 pg/mL, p<0.05) were significantly elevated. These changes were associated with left ventricular dilatation (LVEDD 58±1 mm, p<0.05) and reduced ejection fraction (34.7±1.8%, p<0.05). Conclusion. The findings suggest that inflammatory markers play a crucial role in assessing the severity and prognosis of dilated cardiomyopathy and chronic heart failure.